FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI DI BAGIAN ADMINISTRASI KEUANGAN DAN PELAYANAN PADA RUMAH SAKIT UMUM DAERAH PELALAWAN - Kevin Ariadharma (PEKBIS, 2020)
This study aims to examine the effect of perceptions of organizational support,organizational culture, work competency, work motivation and roles of perception,on the performance of employees with the object of research in The FinancialAdministration and Services at The Pelalawan Regional General Hospital. Thesampling method uses a sampling census and sampling using an error rate of 5%.The author conducts research based on data collection techniques throughquestionnaires. Analysis of the data used is quantitative, analysis of data throughmultiple linear regression equations with t test and test of coefficient of determination(Adj.R2) and data collected and processed with the help of SPSS 25.0 statisticalprogram. From the results of the study the following conclusions are obtained basedon the results of the t test, it is known that the five variables with values (1.512,5.025, 6.901, 4.656 and 1.382). It can be seen that perceptions of organizationalsupport, organizational culture, work competency, work motivation and role ofperceptions have a significant effect on employee performance in the FinancialAdministration and Services of Pelalawan Regional General Hospital. In addition, itcan be seen from the results of the coefficient of determination test (Adj. R2) wherethe value of Adj.R2 is 0.835 (83.5%). It can be seen that employee performance isinfluenced by the five variables, while (16.5%) is influenced by variables others notincluded in this study.